Jugend - Ernährungsstil - Bildung: zu den Perspektiven einer lebensstilorientierten Didaktik der Ernährung - Konstantin von Normann (Westfälische Wilhelms-Universität Münster, Institut für Ökonomische Bildung (IÖB), 2006)
Children adopt unhealthy adult food patterns at the latest by the age of four. This critical food and health behaviour acquired in childhood and youth has a considerable impact on adult disease and mortality rates. Consequently, a decision to adopt healthy eating habits will have a positive influence on quality of life. Empirical lifestyle research and in particular empirical research on food styles has recently provided a series of important works on food style typologies. Empirical knowledge on the development and manifestation of food styles has so far only been available in a somewhat fragmented manner, so that a research gap is clearly evident. The desire to adopt a particular life(food)style only becomes a real behavioural choice in the second decade of an individual's life. In the context of general education, knowledge about this decision or about parameters and conditions that are conducive to deciding in favour of healthy eating habits, become a significant overall health factor. The purpose of this article is to discuss food style typologies and to derive some initial concepts for developing a consistent lifestyle-oriented didactic on diet and to initiate a debate on these issues.
Keywords: I12; I20; Z13; 330; Lifestyle; Deutschland